Chitosan and Chitosan Nanoparticles Differentially Alleviate Salinity Stress in Phaseolus vulgaris L. Plants - Mekhled M. Alenazi; Aya M. El-Ebidy; Omar A. El-shehaby; Mahmoud F. Seleiman; Khalid J. Aldhuwaib; Heba M. M. Abdel-Aziz (Plants, 2024)
Salinity stress can significantly cause negative impacts on the physiological and biochemical traits of plants and, consequently, a reduction in the yield productivity of crops. Therefore, the current study aimed to investigate the effects of chitosan (Cs) and chitosan nanoparticles (CsNPs) to mitigate salinity stress (i.e., 25, 50, 100, and 200 mM NaCl) and improve pigment fractions, carbohydrates content, ions content, proline, hydrogen peroxide, lipid peroxidation, electrolyte leakage content, and the antioxidant system of Phaseolus vulgaris L. grown in clay–sandy soil. Methacrylic acid was used to synthesize CsNPs, with an average size of 40 ± 2 nm. Salinity stress negatively affected yield traits, pigment fractions, and carbohydrate content. However, in plants grown under salt stress, the application of either Cs or CsNPs significantly improved yield, pigment fractions, carbohydrate content, proline, and the antioxidant system, while these treatments reduced hydrogen peroxide, lipid peroxidation, and electrolyte leakage. The positive effects of CsNPs were shown to be more beneficial than Cs when applied exogenously to plants grown under salt stress. In this context, it could be concluded that CsNPs could be used to mitigate salt stress effects on Phaseolus vulgaris L. plants grown in saline soils.